Building the Independent Character of Elementary School Students - Fitri Indriani; Wahidatul Asfia (The Indonesian Institute of Science and Technology Research, 2023)
The cultivation of independent character among elementary school students is crucial in the 21st century. Strong character traits such as empathy, integrity, responsibility, and resilience help students navigate challenges and make positive contributions to their communities. This research focuses on the development of independent character among students during the COVID-19 pandemic. A descriptive research method with a qualitative approach was used, involving observation, interview, and documentation as data collection techniques. The subjects of the research were the school principal, teachers, students, and parents. The data was analyzed through source triangulation techniques to identify opportunities and challenges in the development of character, including in-class learning activities, school culture, and extracurricular activities. In-class learning provides a foundation of knowledge and values, while the school community creates a supportive and inclusive environment. Extracurricular activities allow students to develop skills and interests and expose them to new experiences. Effective integration of these three elements helps students become well-rounded and independent individuals.